Improvement of microstructure and mechanical properties in Wire + Arc Additively Manufactured Ti-6Al-4V with Machine Hammer Peening. (2017) - Hönnige, Jan Roman; Colegrove, Paul; Williams, Stewart
Abstract: Inter-pass rolling is a cold-working technique to improve microstructure and associated mechanical properties in Ti-6Al-4V wire + arc additive manufacturing (WAAM) [1]. Initially developed to eliminate residual stress and distortion in WAAM, rolling equipment is cumbersome and the application is limited to simple features and geometries. To exploit the potential design freedom of AM processes, this study investigates the potential of novel machine hammer peening (MHP) tools to complement or replace rolling as inter-pass cold working technique, as these tools can be manipulated easily with a greater degree of freedom. The cold working behaviour of the tool was assessed using EBSD plastic strain maps, as well as hardness and residual stress profiles. After the tool characterisation, inter-pass peening was applied to Ti-6Al-4V WAAM walls. The successfully achieved grain refinement has met the expectations.